VD_FINDINFO Jug / 2012 / 66 vom 16. September 2011 - VD Tribunal cantonal (2011)
CONSTATATION DES FAITS, MISE EN DANGER DE LA VIE D'AUTRUIART. 129 CP | 129 CP, 47 CP, 63 CP, 398 al. 3 let. b CPP (CH), 399 al. 4 CPP (CH)